2014
DOI: 10.1128/genomea.00054-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Rhodococcus rhodochrous Strain ATCC 21198

Abstract: Rhodococcus rhodochrous is a Gram-positive red-pigmented bacterium commonly found in the soil. The draft genome sequence for R. rhodochrous strain ATCC 21198 is presented here to provide genetic data for a better understanding of its lipid-accumulating capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…Annotation of the draft genome sequence of KG-21 also revealed several genes that may help produce large amounts of lipids in the form of triacylglycerols (TAGs), due to the high activity of enzymes, like wax ester synthase/diacylglycerol acyltransferase, acetyl-coenzyme A (CoA) carboxylase, acyl carrier proteins, (1-acylglycerol-phosphate) acyltransferase, glycerol kinase, and glycerol-3-phosphate dehydrogenase, as reported earlier for R. rhodochrous strain ATCC 21198 ( 9 ). In addition, it also has genes for cytochrome P450 monooxygenase and several peroxidases, oxygenases, and lipases.…”
Section: Genome Announcementsupporting
confidence: 59%
“…Annotation of the draft genome sequence of KG-21 also revealed several genes that may help produce large amounts of lipids in the form of triacylglycerols (TAGs), due to the high activity of enzymes, like wax ester synthase/diacylglycerol acyltransferase, acetyl-coenzyme A (CoA) carboxylase, acyl carrier proteins, (1-acylglycerol-phosphate) acyltransferase, glycerol kinase, and glycerol-3-phosphate dehydrogenase, as reported earlier for R. rhodochrous strain ATCC 21198 ( 9 ). In addition, it also has genes for cytochrome P450 monooxygenase and several peroxidases, oxygenases, and lipases.…”
Section: Genome Announcementsupporting
confidence: 59%
“…When grown in liquid cultures, the growth rate on guaiacol was 0.2 h −1 , which is slightly higher than the growth of the same strain on vanillin (0.127 h −1 ) and 4-HBA (0.126 h −1 ) [ 17 ]. Some species of Rhodococcus have previously been reported to be able to grow on guaiacol [ 78 80 ] or possess genes related to guaiacol breakdown [ 81 ]. The sequence of the enzyme (Cytochrome P450, UniProtKB: W4A0P3) responsible for the conversion of guaiacol to catechol from R. rhodochrous (ATCC 21198) [ 81 ] was blasted against the genome of the R. opacus (taxid: 37919) and an identity of 81% was found, which strongly indicates the presence of a similar protein.…”
Section: Discussionmentioning
confidence: 99%
“…Some species of Rhodococcus have previously been reported to be able to grow on guaiacol [ 78 80 ] or possess genes related to guaiacol breakdown [ 81 ]. The sequence of the enzyme (Cytochrome P450, UniProtKB: W4A0P3) responsible for the conversion of guaiacol to catechol from R. rhodochrous (ATCC 21198) [ 81 ] was blasted against the genome of the R. opacus (taxid: 37919) and an identity of 81% was found, which strongly indicates the presence of a similar protein. When the same enzyme was blasted against the genome of KT2440, no similar protein was found and with P. fluorescens (taxid: 294) only a protein with low identity (28%) was found.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that PrMO is not the only propane‐oxidizing enzyme utilized by the biostimulated microorganisms to oxidize propane. Several recent reports have indicated that propane‐oxidizing bacteria often possess and express genes for more than one hydrocarbon‐oxidizing enzyme during growth on this substrate (Crombie and Murrell 2014; Shields‐Menard et al ; Cappelletti et al ; He et al ; Bennett et al ).…”
Section: Introductionmentioning
confidence: 99%